To determine which student is incorrect, we must carefully analyze each student's work to identify any errors in their calculations or factoring.
Jamal's Work:
-
Step 1: Correctly set the equation to 0: \[ x^2 + 4x - 5 - 7 = 0 \Longrightarrow x^2 + 4x - 12 = 0 \] (This is correct).
-
Step 2: Factoring \(x^2 + 4x - 12 = 0\): \[ (x + 6)(x - 2) = 0 \] (This is also correct since \(6 \times (-2) = -12\) and \(6 + (-2) = 4\)).
-
Step 3: Setting each factor equal to 0: \[ x + 6 = 0 \quad \text{and} \quad x - 2 = 0 \]
-
Step 4: Solving for \(x\): \[ x = -6 \quad \text{and} \quad x = 2 \]
George's Work:
-
Step 1: Did not correctly set the equation to 0: \[ x^2 + 4x - 5 = 7 \Longrightarrow x^2 + 4x - 12 = 0 \]
- This step should match Jamal’s.
-
Step 2: Incorrectly factored the equation: \[ (x + 5)(x - 1) = 7 \]
- This factored form is incorrect. The proper factors should result from the quadratic \(x^2 + 4x - 12\), which Jamal found correctly.
-
Step 3: Setting factors equal to 0 doesn’t apply since the factors are wrong.
-
Step 4: The solutions \(x = -5\) and \(x = 1\) derived from George’s incorrect factorization are also invalid.
Conclusion:
George is incorrect. His initial factoring of the quadratic equation is flawed, as he did not provide the correct factors for \(x^2 + 4x - 12\). Instead of finding the accurate factors and roots, he has derived incorrect answers from incorrect premises. Therefore, the solutions he provided are not valid.